Change in functioning profile after cervical surgery. Issue 1 (23rd November 2022) - Widbom-Kolhanen, Sara S.; Pernaa, Katri I.; Saltychev, Mikhail
Abstract : The objectives are to (a) introduce an approach to use the Neck Disability Index (NDI) in a way, which is different and more International Classification of Functioning, Disability and Health-oriented than acommon practice – focusing on functional profile instead of composite score only, and (b) to describe the changes in functioning experienced by patients undergoing cervical surgery. This was a register-based study of almost 400 patients undergoing different cervical surgical procedures in a university hospital between 2018 and 2021. The patients responded to repeated surveys preoperatively and 3, 12 and 24 months postoperatively. Linear regression test was performed to analyze the change of the NDI score. The changes in scores during a follow-up were statistically significant ( P < 0.001) for all the NDI items as well as for the total score. Each item demonstrated significant improvement postoperatively and a slight worsening between 1 and 2 years after the surgery. The observed slight decline in functioning at the end of follow-up remained below the baseline level for all the items. While the change in the composite score of the NDI was able to describe the overall change in functioning after the surgery, different areas of functioning were affected by the surgery differently. The results suggest that the use of functional profiles, in addition to composite scores, is justified among patients with cervical pathologies.